IMPLEMENTASI STRATEGI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MANAJEMEN KONSTRUKSI UNTUK MENGEMBANGKAN ETIKA PROFESIONAL MAHASISWA TEKNIK SIPIL - Manurung, Edison Hatoguan; Hutagaol, Kerlima; Dasrah, Irvon (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research examines the implementation of character education strategies in the digital era, focusing on the integration of fundamental values and modern technology. Using a qualitative approach with library research methods, this study analyzes various current literature sources to understand the dynamics of character education in the context of digital transformation. The results show that effective implementation of character education requires a holistic approach encompassing three main dimensions: development of adaptive philosophical foundations, integrated implementation strategies, and multi-stakeholder collaboration. The comprehensive evaluation framework developed includes cognitive, affective, and psychomotor aspects, emphasizing the importance of continuous monitoring. Major challenges in implementation include digital gaps and socio-cultural diversity, requiring contextual adaptation strategies. The proposed sustainable development model integrates environmental values and sustainable development, considering aspects of program scalability and replication. This research contributes to the development of the body of knowledge on character education in the digital era and provides a practical framework for implementing effective and sustainable character education programs.